Implementation of Cooperative Learning Model “Think Pair And Share" on English Learning Outcomes - Siska Anggita Situmeang; Irene Adryani Nababan; Sanggam Siahaan; Ony Maretta Sinurat; Cantika May Maria Sirait; Kevin William Andri Siahaan (Jurnal Pendidikan Edutama, 2022)
Group Teaching Activities Help Promote Active Learning Classroom teaching and learning activities can aid teaching, but the ability to teach through small group collaborative activities primarily facilitates active, active teaching activities. This study aims to determine the difference between students' English learning outcomes using the Expository method and students' English learning outcomes using the Think Pair Share (TPS) collaboration model. Samples were taken as many as 50 students from 2 groups, namely the experimental group and the control group. The research method used by the author is experimental. The sample collection technique used is a simple random sample collection technique. Hopefully the purpose of this research can be useful for students, teachers, schools, and especially researchers. The data analysis technique used is at a significant level = 0.05 tcount = 2.893 and ttable = 2.0252 It can be concluded that the number of students who apply "Think Pair Share" (TPS) is more than the number of students who learn through Exposure Learning.